Peranan Kepala Daerah dalam Mendidik Karakter Pelajar yang Baik untuk Menciptakan Generasi Unggul - Irawati, Sri Ayu; Muhsinin, Muh. Irfan (Ideas Publishing, 2025)
Character education is an important foundation in the formation of student character and the role of regional heads in supporting the process of superior character education. This study aims to analyze the role of regional heads in educating student character and its impact on creating a superior generation. The research method used is descriptive qualitative. The results of the study indicate that regional heads play a role through the preparation of character education policies, facilitating moral value development activities in schools, and cross-sector collaboration to support sustainable character education. This study concludes that the active involvement of regional heads is able to encourage the creation of a generation that is intelligent and strong in morals and ethics